Association of adiposity with diabetes: A national research among Chinese adults. Issue 5 (24th July 2020) - Fu, Wenning; Wang, Chao; Zou, Li; Jiang, Heng; Miller, Mia; Gan, Yong; Cao, Shiyi; Xu, Hongbin; Mao, Jing; Yan, Shijiao; Yue, Wei; Yan, Feng; et al.
Abstract: Background: Adiposity is an established risk factor for diabetes. The different measurements of adiposity for predicting diabetes have been compared in recent studies in Western countries. However, similar researches among Chinese adults are limited. Methods: Data were collected from a national survey conducted during September 2014 and May 2015 Among Chinese adults aged 40 years and older across 30 China's provinces. Multilevel model analysis was performed to examine the impacts of different obesity indices [body mass index (BMI), waist circumference (WC), lipid accumulation product index (LAP), visceral adiposity index (VAI), and body adiposity index (BAI)] on the risk of diabetes. Results: A total of 162 880 participants were included in this study. Of them, 54.47% were female. With an increase in BMI, WC, LAP, VAI, and BAI, the prevalence of diabetes significantly grew ( P  < 0.001). The multilevel model analysis showed that WC has the strongest impact on diabetes prevalence, while BAI was the weakest. For one SD increment in BMI, WC, LAP, VAI, and BAI, the prevalence of diabetes increased by 27.0% ( Odds Ratio (OR)  = 1.270, 95% Confidence interval (CI)  = 1.251–1.289), 37.4% ( OR  = 1.374, 95% CI = 1.346–1.401), 28.1% ( OR  = 1.281, 95% CI  = 1.266–1.297), 22.0% ( OR  = 1.220, 95% CI = 1.204–1.236), and 17.4% ( OR  = 1.174, 95% CI  = 1.151–1.192), respectively. Conclusion: Obesity indicators of BMI, WC, LAP, VAI, and BAI have significant positive relationships with the risk of diabetes. WC has the strongest impact on diabetes, while BAI has the weakest.